PEMAHAMAN DAN PENGHAYATAN PESERTA DIDIK TENTANG IBADAH DALAM PEMBELAJARAN FIQIH DI MI NEGERI 20 HST - Ubaidillah Ubaidillah (ADISAM PUBLISHER, 2023)
The purpose of this research was to find out what are the practices of students’ worship and how students understand and appreciate their worship. This research was a field research with qualitative data analysis. Data analysis was carried out through some steps, namely data collection, data reduction, data presentation and conclusion drawing. Test the validity of the data using triangulation. The results of this study showed that the worship activities taught and accustomed to students were prayer, fasting, daily prayer, reading and memorizing the Qur’an. The students understood the laws of worship such as compulsory, sunna, sin, reward, heaven and hell. However, they do not yet understand about the purpose and benefits of worship that it does. The practice of worship of students was classified as obedient and has become a daily habit. This shows that the practice of students’ worship has become a personality (being / moral action) but is still weak in understanding (moral knowledge) and has not yet reached awareness (moral feelings).